2012
DOI: 10.1186/1556-276x-7-136
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of transparent lead-free KNN glass ceramics by incorporation method

Abstract: The incorporation method was employed to produce potassium sodium niobate [KNN] (K0.5Na0.5NbO3) glass ceramics from the KNN-SiO2 system. This incorporation method combines a simple mixed-oxide technique for producing KNN powder and a conventional melt-quenching technique to form the resulting glass. KNN was calcined at 800°C and subsequently mixed with SiO2 in the KNN:SiO2 ratio of 75:25 (mol%). The successfully produced optically transparent glass was then subjected to a heat treatment schedule at temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The average crystallite size is about 100 nm in length and 10 nm in diameter, which is small enough to reduce the light scattering and giving rise to high transparency of this sample. This result is consistent with our previous works [11,12], which have found that high heat treatment temperature increased the crystalline size, leading to the increase light scattering and decreased the light transmission in glass-ceramics until opaque. The FE-SEM micrograph in Fig.…”
Section: Microstructure Of Glass Ceramics By Fesem and Temsupporting
confidence: 95%
See 1 more Smart Citation
“…The average crystallite size is about 100 nm in length and 10 nm in diameter, which is small enough to reduce the light scattering and giving rise to high transparency of this sample. This result is consistent with our previous works [11,12], which have found that high heat treatment temperature increased the crystalline size, leading to the increase light scattering and decreased the light transmission in glass-ceramics until opaque. The FE-SEM micrograph in Fig.…”
Section: Microstructure Of Glass Ceramics By Fesem and Temsupporting
confidence: 95%
“…KNN powder was firstly prepared by conventional mixed oxide method according to our previous work [11,12]. For incorporation method, the prepared KNN ceramic powder was then mixed with SiO 2 , in order to form transparent based glass.…”
Section: Sample Preparationmentioning
confidence: 99%
“…The packing density of the annealed films was calculated by using following equation,P=nnormalf21nnormalf2+2nnormalb2+2nnormalb21where, n b is the bulk KNN refractive index (2.2) of KNN and n f is the observed film refractive index (at 700 nm). The thicknesses of the films were found to be in the range of 280–300 nm and 260–290 nm for as‐deposited and annealed films, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve splendid optical transparency of ceramics, particularly high density with quite low porosity, absence of impurities, small‐sized grains, high crystal symmetry as well as very smooth surface are usually indispensable to extremely eliminate light scattering . Ferroelectric transparent ceramics, such as (Pb 1− x La x )(Zr y Ti 1− y ) 1− x /4 O 3 (PLZT), were first developed to combine the multielectrical properties of ferroelectric crystals with the transparency of a material matrix, making them suitable for the potential applications of smart phones, high‐power lasers, e‐readers, optical switches, optical integrated circuit, optical resonators, and microwave devices …”
Section: Introductionmentioning
confidence: 99%